Visual assessment by psychophysical methods of people subjected to occupational exposure to organic solvents (Psicologia USP, 2011)
Organic solvents are neurotoxic substances that can cause damaging effects in the visual system. Occupational exposure to these substances is common because they are used in a wide variety of activities. These effects can be quantified by specific psychophysical tests. The most commonly used tests for color vision assessment are arrangement tests, such as the Lanthony Panel D-15 desaturated test and the Farnsworth-Munsell 100-hue test, and for contrast sensitivity assessment, printed panel tests such as the MCT 8000 VISTECH, VCTS 6500VISTECH, and FACT 101 tests. Generally, these tests show color discrimination losses in the blue-yellow and red-green axis, and a decrease in contrast sensitivity, mainly at low spatial frequencies. There is a positive correlation between psychophysical results and biological environmental markers, but this correlation depends on the marker and on the kind of solvent to which the individuals are exposed. Factors such as alcohol and tobacco can interfere with the correlation of the results.